2014
DOI: 10.1021/nn4064924
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation Effects of High-Energy Proton Beams on MoS2Field Effect Transistors

Abstract: We investigated the effect of irradiation on molybdenum disulfide (MoS2) field effect transistors with 10 MeV high-energy proton beams. The electrical characteristics of the devices were measured before and after proton irradiation with fluence conditions of 10(12), 10(13), and 10(14) cm(-2). For a low proton beam fluence condition of 10(12) cm(-2), the electrical properties of the devices were nearly unchanged in response to proton irradiation. In contrast, for proton beam fluence conditions of 10(13) or 10(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 42 publications
4
87
0
Order By: Relevance
“…This fluence corresponds to a relatively high radiation dose in comparison to doses known to induce effects on the operation of TMD transistors. For example, trapped charges in dielectrics such as silicon dioxide can degrade the device electrical characteristics of TMD transistors at a dose level that is two to three orders of magnitude lower than used in this experiment 26 , suggesting that degradation in TMD-based device architectures is not due to the TMD layer, but surrounding materials. The XPS peak shift observed in our experiment can be interpreted as charge transfer due to a combination of direct damage to WSe 2 , indirect effects from the substrate, and carrier trapping by interface states.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…This fluence corresponds to a relatively high radiation dose in comparison to doses known to induce effects on the operation of TMD transistors. For example, trapped charges in dielectrics such as silicon dioxide can degrade the device electrical characteristics of TMD transistors at a dose level that is two to three orders of magnitude lower than used in this experiment 26 , suggesting that degradation in TMD-based device architectures is not due to the TMD layer, but surrounding materials. The XPS peak shift observed in our experiment can be interpreted as charge transfer due to a combination of direct damage to WSe 2 , indirect effects from the substrate, and carrier trapping by interface states.…”
Section: Resultsmentioning
confidence: 81%
“…We thus expect that at this total ionizing radiation dose level, a device based on this heterostructure would be damaged beyond repair due to heavy damage to the WSe 2 channel. In conclusion, due to the absence of chemical modifications of WSe 2 via XPS and the observation of charging effect only at very high proton fluence level, we expect the radiation resilience of TMD-based transistors to be limited by the dielectric insulator and the substrate, which would degrade at a much lower proton fluence level 26, 56 . The WSe 2 structural change after heavy ion bombardment indicates the impact of nuclear stopping power on these ultra-thin materials.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…13,14 In addition to the native defects unintentionally introduced during growth, defects may also be produced deliberately at the postgrowth stage. [15][16][17] There are various types of structural defects in MoS 2 , such as point defects, 13 dislocations, 18 grain boundary, 19 or topological. 20 The point defect is one of the native defects which have been studied both in experiment 13 and theory.…”
Section: Introductionmentioning
confidence: 99%
“…Irradiation with charged particle beams allows precise control of defect generation by altering beam conditions and exposure dose [8]. Kim et al have shown the use of a high energy proton beam to introduce trap states in the back gate dielectric of a MoS2 thin-film transistor [10]. Tongay et al have used α-particle irradiation to generate vacancies in TMDCs, which give rise to new emission peaks with enhanced photoluminescence intensity [11].…”
Section: Introductionmentioning
confidence: 99%